1999
DOI: 10.1029/1999gl005370
|View full text |Cite
|
Sign up to set email alerts
|

Seismic tomographic inversion of Russian PNE data along profile Kraton

Abstract: Abstract. Tomographic inversion of Russian peaceful nuclear explosion (PNE) data collected along the 3500 km east-west striking profile Kraton has provided new information about the two-dimensional P-wave velocity structure of the upper mantle beneath the Siberian platform. The 8 ø discontinuity is clearly identified as the top of a zone in the 100-200 km depth range. This zone appears as a low-velocity zone in large parts of the profile and has zero velocity gradient along the profile. The 400 km discontinuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…According to travel-time inversion of seismic data along the PNE profiles Quartz and Kraton, this feature extends eastwards as a continuous layer for at least 3000 km into the West Siberian Basin and the Siberian Shield (Nielsen et al 1999). Similar reduced-velocity layers have been reported earlier for other cratonic regions of the world (Grand & Helmberger 1984;LeFevre & Helmberger 1989;Pavlenkova et al 1996;Darbyshire 2005) and suggest that it may be a global characteristic of Precambrian lithosphere (Thybo & Perchuc 1997;Thybo 2006).…”
Section: Figsupporting
confidence: 78%
See 1 more Smart Citation
“…According to travel-time inversion of seismic data along the PNE profiles Quartz and Kraton, this feature extends eastwards as a continuous layer for at least 3000 km into the West Siberian Basin and the Siberian Shield (Nielsen et al 1999). Similar reduced-velocity layers have been reported earlier for other cratonic regions of the world (Grand & Helmberger 1984;LeFevre & Helmberger 1989;Pavlenkova et al 1996;Darbyshire 2005) and suggest that it may be a global characteristic of Precambrian lithosphere (Thybo & Perchuc 1997;Thybo 2006).…”
Section: Figsupporting
confidence: 78%
“…8c). This highly reflective layer with reduced seismic velocities extends for 3000 km further eastwards (Thybo & Perchuc 1997) and is underlain by a high-velocity layer at c. 200-250km depth (Nielsen et al 1999;Kuzin 2001). Seismic reflection profiling of the Southern Urals (Knapp et al 1996) revealed mantle reflections at depths of c. 80 km and 175 km; the lower reflector was interpreted as possibly imaging the base of the lithosphere.…”
Section: The Uralidesmentioning
confidence: 99%
“…A low-velocity zone in the cratonic upper mantle near 100 km depth has frequently been observed in controlled source (including nuclear explosions) seismic data (Nielsen et al, 1999;Thybo, 2006;Thybo and Perchuc, 1997). The Svekalapko Seismic Tomography Working Group (2004) found the LAB at 100-130 km depth below Finland in wideangle data.…”
Section: Europe and The Middle Eastmentioning
confidence: 98%
“…Parker et al (1984) observed below the Rio Grande Rift an upwarp of the asthenosphere from P residuals. Nielsen et al (1999) located the 8 discontinuity at 100-200 km depth from nuclear explosion data on the Siberian platform (8 discontinuity is frequently also interpreted as LAB; Thybo (2006)). Nielsen et al (1999) located the 8 discontinuity at 100-200 km depth from nuclear explosion data on the Siberian platform (8 discontinuity is frequently also interpreted as LAB; Thybo (2006)).…”
Section: The Gutenberg Discontinuitymentioning
confidence: 99%